2019
DOI: 10.12957/reuerj.2019.38670
|View full text |Cite
|
Sign up to set email alerts
|

Estratégias para o fortalecimento da cultura de segurança em unidades de terapia intensiva [Strategies for strengthening safety culture in intensive care units] [Estrategias para el fortalecimiento de la cultura de seguridad en unidades de cuidados intensivos]

Abstract: Objetivo: identificar estratégias de promoção que contribuam para o fortalecimento da cultura de segurança do paciente em unidades de terapia intensiva. Método: estudo qualitativo, descritivo, realizado com cinco médicos, cinco enfermeiros e 24 técnicos de enfermagem atuantes em unidades de terapia intensiva de duas instituições hospitalares do sul do Brasil em 2016. A coleta dos dados foi realizada por meio de entrevistas semiestruturadas e o tratamento, pela análise textual discursiva. A pesquisa foi aprovad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
(17 reference statements)
0
4
0
6
Order By: Relevance
“…Those difficulties can negatively impact care and, in turn, patient safety. In a study conducted in two ICUs in southern Brazil, participants (doctors, nurses, and nursing technicians) pointed out that the implementation of protocols, the insertion of discussions about patient safety in PEH strategies, and the involvement of professionals and institution are measures that can be adopted to promote skills and attitudes committed to patient safety (32) .…”
Section: Discussionmentioning
confidence: 99%
“…Those difficulties can negatively impact care and, in turn, patient safety. In a study conducted in two ICUs in southern Brazil, participants (doctors, nurses, and nursing technicians) pointed out that the implementation of protocols, the insertion of discussions about patient safety in PEH strategies, and the involvement of professionals and institution are measures that can be adopted to promote skills and attitudes committed to patient safety (32) .…”
Section: Discussionmentioning
confidence: 99%
“…As falas do estudo deixam transparecer que a estratégia para auxiliar a mudança da cultura de segurança foram a elaboração e a implantação de novos protocolos, diretrizes e ferramentas de cuidados que apoiassem o enfermeiro na investigação junto a familiares e profissionais da saúde, além de ferramentas que asseguram a continuidade da assistência ao potencial doador, mesmo diante do risco de contaminação pelo vírus SARS-CoV-2. A estratégia de utilização de protocolos de segurança do paciente é um estímulo para a prática assistencial segura e para o fortalecimento da cultura de segurança em cenários de cuidado 21,22 .…”
Section: Discussionunclassified
“…Thus, it is observed that the themes developed were of fundamental importance for the Nursing team to provide quality and risk-free care. 13 In Intensive Care, it is understood that patients are considered at risk for adverse events, which requires professionals to perform complex care, attention, agility and know how to deal with technologies, 14 which demonstrates the importance and the need to always carry out training in this sector. It should be noted that the ICU is a highly complex hospital sector that requires continuity of service and the dedication of professionals to transform the environment in which they work.…”
Section: Article Codementioning
confidence: 99%